Crosslinking biopolymers for biomedical applications. Issue 6 (June 2015) - Reddy, Narendra; Reddy, Roopa; Jiang, Qiuran
Highlights: Biopolymeric materials are preferred for medical applications. Biopolymeric materials lack the desired mechanical properties and aqueous stability. Crosslinking is carried out to improve properties but is potentially cytotoxic. Green chemicals and new technologies for crosslinking need to be developed. Abstract : Biomaterials made from proteins, polysaccharides, and synthetic biopolymers are preferred but lack the mechanical properties and stability in aqueous environments necessary for medical applications. Crosslinking improves the properties of the biomaterials, but most crosslinkers either cause undesirable changes to the functionality of the biopolymers or result in cytotoxicity. Glutaraldehyde, the most widely used crosslinking agent, is difficult to handle and contradictory views have been presented on the cytotoxicity of glutaraldehyde-crosslinked materials. Recently, poly(carboxylic acids) that can crosslink in both dry and wet conditions have been shown to provide the desired improvements in tensile properties, increase in stability under aqueous conditions, and also promote cell attachment and proliferation. Green chemicals and newer crosslinking approaches are necessary to obtain biopolymeric materials with properties desired for medical applications.